Pengaruh Motivasi, Kerjasama Tim Dan Komunikasi Terhadap Kinerja Karyawan (Studi Pada Pt. Kebon Agung Pg Trangkil Pati) - Muhamad Andi Usman; Askar Yunianto (STIE Amkop Makassar, 2023)
Kebon Agung Trangkil Pati Sugar Factory is one of the companies in Indonesia that processes sugar cane into sugar. In achieving its goals, companies experience problems with lack of motivation, teamwork, and communication which causes the performance of human resources to decline making it difficult to achieve organizational goals in the form of wages, worker guarantees, and working conditions. The purpose of this study was to determine the effect of motivation, teamwork, and communication on the performance of employees of PT Kebon Agung PG Trangkil Pati.This research is a quantitative research with correlational method. The population in this study amounted to 100 employees and the entire population was sampled in this study. Data collection techniques using a questionnaire. The research instrument was tested using validity and reliability tests. Data analysis techniques using multiple linear regression analysis, F test, T test and analysis of the coefficient of determination.The results of the analysis of the coefficient of determination above show an R Square value of 0.218. Thus it can be stated that the X variable of motivation, teamwork, and communication has a relationship to the performance variable (y) of 21.8%, the rest is influenced by other factors not examined in this study.The calculated t value of the motivation variable is 2,541 with a significance value of 0.013 which indicates that motivation has a significant relationship and has a low effect on employee performance. The t value for the Teamwork variable is 2,337 with a sig. 0.022 which shows that teamwork has a significant relationship and low influence on employee performance. The t value of the communication variable is 2,541 with a sig. 0.033 which shows that communication has a significant relationship and low influence on employee performance.